The Role of the Interlocking Director and Board Receptivity in the Diffusion of Practices - Shropshire, Christine (Academy of Management Review, 2010)
Board interlocks are frequently examined as conduits of practices between firms. I propose that variance among the individual directors who create these linkages affects the likelihood information is transmitted across them. Further, I discuss organizational characteristics that shape how receptive a board is to the diffusion of practices. I conceptualize a model to investigate, first, which directors are more likely to transmit experience or knowledge about organizational practices and, second, what factors influence how that information is received.